INSTALLASI DESAIN DAN PENGEMBANGAN JARINGAN KOMPUTER BERSKALA KECIL (STUDI KASUS : INSTALASI ONLINE WIRELESS DI RUMAH ) - Agus Dendi Rachmatsyah (LPPM Universitas Bina Sarana Informatika, 2009)
Computer and network technology evolve very rapidly and is advancing. There are a lot of connectedcomputers in the network which facilitate effective and efficient working activities. This also increases theefficiency in computer usage since many resources are available at the same time. In this writing, theauthor uses library research and direct observation. Based on the case study done on the installationdesign of small-scale computer network at home and at work, it can be concluded that the small-scalecomputer network is very appropriate to be applied in housing and in the community. It is due to theincreasing needs on technology in Indonesia, especially in the field of computers and wireless technology,simple computers without a LAN card and the wireless (wifi) suitable for workplaces and homes.Keyword: wireless, network, internet protocol